Preliminary evidence of safety and effectiveness of Loxoprofen Sodium Cataplasm combined with physiotherapy for myofascial pain syndrome treatment: A randomized controlled pilot clinical trial - Zhou, Xuewen; Li, Xuelian; Wang, Ziyang; Huang, Dong (Frontiers in neurology, 2022)
Myofascial pain syndrome (MPS) is one of the most common causes of chronic skeletal muscle pain, which is closely related to skeletal muscle myofascial trigger point (MTRP). Since there is no first-line treatment for MPS, we investigated Loxoprofen Sodium Cataplasm combined with physiotherapy as a non-invasive therapy in patients at different levels to a protocol with superior efficacy that is safe and easy to promote. Moreover, this treatment could represent an alternative therapeutic strategy for low-income patients to a safer, more convenient, and more economical treatment scheme. A randomized clinical study was aimed at evaluating the safety and efficacy of Loxoprofen Sodium Cataplasm combined with physiotherapy in patients diagnosed with MPS in the pain clinic. We screened 100 patients with MPS, and using a computer-generated random allocation sequence, we stratified patients in a ratio of 2:1:1:1 (A: B: C: D) to one of the four treatment groups. Group A received Loxoprofen Sodium Cataplasm combined with extracorporeal shock wave therapy (ESWT) and transcutaneous electrical nerve stimulation (TENS). Group B received Loxoprofen Sodium Cataplasm alone. Group C received physiotherapy alone. Group D received Flurbiprofen Cataplasm combined with physiotherapy. After 2 weeks of treatment, the overall efficiency and secondary assessment indicators, including visual analog scale (VAS) scores, chronic soft tissue injury (CSTI) scores, Oswestry Disability Index (ODI) scores, or Northwick Park Neck Pain Questionnaire (NPQ) scores, were evaluated before and after treatment to analyze the difference in efficacy of each group. All groups were well tolerated with no reported adverse events. Significant treatment differences in the change from baseline in overall efficiency (primary efficacy endpoint) ( = 0.0078) were observed in subjects of groups A and C. Showing valuable data of efficacy in primary and secondary endpoints, Loxoprofen Sodium Cataplasm combined with physiotherapy is superior in the treatment of MPS. https://www.chictr.org.cn/ (ChiCTR2100054756).